Research on the Development Course of Economic Innovation and the Growth Mode of Financial Profit of Google - Wang Nuowen (SHS Web of Conferences, 2025)
This research examines Google’s transformative trajectory in technological innovation and economic growth, exploring the complex interplay between strategic structural transformation, financial optimization, and technological advancement. Drawing from comprehensive analyses of digital ecosystem evolution, the study reveals how Google has transcended traditional technological boundaries by strategically investing in artificial intelligence, cloud computing, and cross-domain technological solutions. The research demonstrates that Google’s approach to innovation goes beyond incremental improvements, embodying a “10x” principle of radical technological enhancement. The study uncovers how technological innovation drives sustainable financial growth and market leadership by analyzing the company’s multifaceted strategies across advertising, search technologies, mobile services, and platform development. Key findings highlight the potential of generative AI to generate $2.6 to $4.4 trillion annually, with approximately 75% of value concentrated in customer operations, marketing, software engineering, and research domains. The research also critically analyzes technological gaps, particularly in AI alignment and contextual comprehension, revealing significant opportunities for progress. Thus, the study specifying Google’s technological environment could advance comprehension of technological advancement, economic progress and competitive management strategies where Google is seen at the core of knowledge-intensive change possibilities in the digital economy, underlining the importance of constant technological advancement for the contemporary economy settings.